2017
DOI: 10.1097/dss.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Broader Practice Indications for Mohs Surgical Defect Healing by Secondary Intention: A Survey Study

Abstract: Broader indications for SI healing of Mohs surgical defects may be appropriate than previously understood. In addition to concave, temporal, periocular, perinasal, and periauricular sites, SI healing may be appropriate for convex sites such as the scalp and anterior lower extremity, deep wounds, and large wounds, as well as wounds with dehiscence, flap necrosis, or infection. Certain patient-specific and lesional factors are also appropriate indications for SI healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
2
14
0
2
Order By: Relevance
“…A survey study found that the most experienced surgeons were significantly more likely to heal deep and larger wounds secondarily. 8 The use of SIH as a reconstructive option remains very physician and institution dependent as evidenced by a systematic review 1 where SIH was part of a reconstructive ladder, but SIH was not listed as surgical option in a 105 patient, single institution study. 9 SIH over areas of absent periosteum has been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…A survey study found that the most experienced surgeons were significantly more likely to heal deep and larger wounds secondarily. 8 The use of SIH as a reconstructive option remains very physician and institution dependent as evidenced by a systematic review 1 where SIH was part of a reconstructive ladder, but SIH was not listed as surgical option in a 105 patient, single institution study. 9 SIH over areas of absent periosteum has been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…: medial canthus (9), lateral canthus (3), lower eyelid (1). b Among lip subunits: cutaneous lip (4), vermillion lip(8).…”
mentioning
confidence: 99%
“…These three cases demonstrate the effective use of SG to facilitate SI healing of scalp and limb surgical defects. SI healing may be preferable for scalp defects with exposed periosteum and when defects cannot be closed with sutures. There is a shorter surgical time and lower risk of damage to neighbouring structures, and the technique facilitates close surveillance .…”
mentioning
confidence: 99%
“…SI healing may be preferable for scalp defects with exposed periosteum and when defects cannot be closed with sutures. There is a shorter surgical time and lower risk of damage to neighbouring structures, and the technique facilitates close surveillance . The primary disadvantage is prolonged wound care .…”
mentioning
confidence: 99%
See 1 more Smart Citation